The Influence of intrinsic motivation on employee performance in public organizations in Kenya - Nyaga, Agatha Ngithi (Strathmore University, 2021)
The purpose of this study was to establish the int1uence of intrinsic motivation on employee performance in public organizations in Kenya. Intrinsic motivation is important not only with a view to satisfy the needs and e::hrpectations of individual people who work in the public service but also create a feeling of belonging and commitment among the employees. Low motivation in public organizations has been cited as a major factor in Africa's human resource crisis, non-monetary motivators that foster team and organizational commitment are employee recognition, employee development, participatory environment, job security and job autonomy. A descriptive research design was adopted which \vas deemed to be the most appropriate since it permitted the researcher to describe the characteristics of the variables mentioned in the study. The research targeted employees of 65 public organizations in Nairobi County-Kenya which due to various constraints, due to Covid 19 pandemic restrictions only employees of 25 organizations were sampled. 375 employees were sampled using stratified random sampling. Primary data was collected by means of a structured questionnaire,which was self-administered. The data collected ·was analysed using descriptive statistics with the help of Statistical Package for Social Sciences (SPSS) to achieve the objectives of the study. Simple regression analysis and correlation analysis were used to analyse data. The study found that employee development, recognition, job autonomy and employee achievement motivation had significant and positive effect on employee performance. The study recommended that the overall management of public organizational input greater emphasis on recognition and non-monetary reward programs to attain higher employee performance. The management should also give the employees the autonomy to do their jobs which will improve employee attitude and in tum enhance employee performance. The study concluded that employee development has a positive effect on employee performance and that motivation inf1uences job performance but they there are many challenges associated with motivation that are essential to optimize employee performance. This study only focused on employee performance; future studies could focus on both employee and firm performance.
A Research thesis submitted in partial fulfilment of the requirements for the Degree of Master of Commerce at Strathmore University